Fifteen-minute consultation: Fractures in non-ambulant children with cerebral palsy. Issue 1 (23rd December 2020) - Debelle, Geoff; Morris, Helen; Shaw, Nick; Oates, Adam
Abstract : Objective: To describe a safeguarding decision pathway for the assessment of osteopenic fractures in non-ambulant children with cerebral palsy. Method: Literature review and consensus practice of a child safeguarding team, including clinicians and social workers. Conclusion: Low-energy fractures of the lower limb in non-ambulant children with cerebral palsy are relatively common and explained by the presence of reduced bone strength, in the absence of any other unexplained injuries or safeguarding concerns.